STUDI LITERATUR MENGEMBANGKAN KEMAMPUAN BERBAHASA ANAK USIA DINI MELALUI KEGIATAN BERCERITA - Harliana Harliana; Azria Bey Alfina; Hermanto Hermanto (Consilium: Education and Counseling Journal, 2026)
This study aims to develop early childhood language skills through storytelling methods. Early childhood is in its golden age where their development is very rapid and sensitive to various stimuli. Language as a means of communication plays an important role in child development. This study used literature study and interview methods to collect data. Data analysis is carried out with the Miles and Huberman model which includes data reduction, data presentation, and conclusion/verification. The findings showed that the use of media such as picture storybooks, hand puppets, calendar big books, series drawings, finger puppets, and flannel boards can significantly improve children's language skills. These media not only make storytelling activities more interesting but also support the development of receptive and expressive aspects of children's language. The conclusion of this study is that storytelling methods with the support of the right media can be an effective way to develop early childhood language skills.